Prediction of Communication Outage Period between Satellite and Earth station Due to Sun Interference - Yongjun Song; Kap-Sung Kim; Ho Jin; Byoung-Sun Lee (Journal of Astronomy and Space Sciences, 2010)
We developed a computer program to predict solar interference period. To calculate Sun‘s position, we used DE406 ephemerides and Earth ellipsoid model. The Sun‘s position error is smaller than 10arcsec. For the verification of the calculation, we used TU media ground station on Seongsu-dong, and MBSAT geostationary communication satellite. We analysis errors, due to satellite perturbation and antenna align. The time error due to antenna align has -35 to +16 seconds at 0.1 degree, and -27 to +41 seconds at 0.25 degree. The time errors derived by satellite perturbation has 30 to 60 seconds.